Political Conceptual Metaphors in the 2024 Presidential Election on Kompas.com - Aliyah Salsabila Hakim; Elvi Citraresmana; Hera Meganova Lyra (RETORIKA: Jurnal Ilmu Bahasa, 2024)
News about the election, particularly the 2024 presidential election, is currently becoming a hot topic, especially after the presence of three candidates from each political party. Understanding political conceptual metaphors is important because it can be useful for language research and teaching by providing new insights, it can also expand public knowledge about political situations through metaphors. The political parties promoting the candidates are Partai Demokrasi Indonesia (PDI) Perjuangan, Partai Nasional Demokrat (Nasdem), and Partai Gerakan Indonesia Raya (Gerindra). The three candidates supported by these parties are Ganjar Pranowo, Anies Baswedan, and Prabowo Subianto. Current information related to the presidential election is conveyed by media crews through online news sites, including Kompas.com. Previous studies have largely overlooked the 2024 presidential election and often did not employ lexical semantic theory in analyzing political metaphors, creating a gap that this research aims to fill. This research aims to describe the political concepts built through conceptual metaphors in the 2024 presidential election. The method of this research is descriptive-qualitative. Collecting data using note-taking techniques. The referential method was used to analyze data. The data sources from newspapers uploaded by Kompas.com online news sites in the period from June 2023 to January 2024. The results of the research show that there are five metaphorical concepts “Politics is a Plan”, “Politics is a Fight”, “Politics is a Defense”, “Politics is a Game”, and “Politics is a Marriage”.